Opisoma excavatum Boehm, a Lower Jurassic photosymbiotic alatoform‐chambered bivalve. (29th August 2013) - Posenato, Renato; Bassi, Davide; Nebelsick, James H.
<x xml:space="preserve">Abstract</x> Alatoform bivalves are a polyphyletic group characterized by antero‐posteriorly compressed shells and a ventro‐lateral wing originating from a tight fold of the shell wall. This bizarre shell morphology is interpreted as an adaptation for algal photosymbiosis in heliophilous bivalves. The group contains the living heart cockle Corculum together with four extinct genera ranging in age from the Permian to the Jurassic. The Jurassic alatoform bivalve is Opisoma, which has an aragonitic shell that is divided into two regions, both with different functions: one for stabilization, the other for hosting symbionts. The dorsal part of the shell is massive and played the stabilization role. The ventral part has a very thin and fragile shell that permitted the transmission of light into the internal tissues harbouring photosymbionts. The morphology of this delicate ventral part has thus far remained obscure, due to lack of preservation. Accumulations of Opisoma excavatum Boehm with exquisitely preserved shells containing the fragile winged ventral parts are common within the Pliensbachian shallow‐water, lagoonal carbonate succession of the Rotzo Formation of northern Italy. The wings have internal curved chambers limited by septa parallel to the wing edge. The shell of the ventral part consists of irregular fibrous prismatic and homogeneous structures which progressively infill the chambers. As the chambered wings are analogous structures among alatoform bivalves, they are no longer considered a taxonomic character. According to the observed shell orientation in the field and the consequent organization of the soft parts, Opisoma had an opisthogyrate shell.